Psychological outcomes in advanced cancer patients after receiving genomic tumor profiling results - Vatter, Sabina; Schlub, Timothy E; Napier, Christine E; Best, Megan C; Bartley, Nicci; Juraskova, Ilona; Meiser, Bettina; Ballinger, Mandy L; Biesecker, Barbara B; Goldstein, David; Thomas, David M; Butow, Phyllis (Health psychology, 2022)
Comprehensive tumor genomic profiling (CGP) offers hope for personalized treatment for cancer patients when other treatment options have been exhausted. However, receipt of nonactionable or ambiguous results could be an ongoing source of distress. We investigated patterns of hope, anxiety, depression, and CGP-specific anxiety in advanced cancer patients after receiving CGP results and 2-3 months later. Participants were enrolled in a longitudinal psychosocial substudy, embedded in the Molecular Screening and Therapeutics Program, and had advanced solid cancers of any histological type with sufficient and accessible tissue for CGP. At T0 (before receiving CGP results), 1,431 participants completed sociodemographic, disease and psychosocial measures. At T1 (1-4 weeks after receiving CGP results) and T2 (2-3 months post-T1), 374 participants completed psychological outcome measures. Predictors of outcomes at T2 were identified using multinomial logistic regression. Approximately 75% of participants did not experience significant hopelessness or distress at T1 and T2. Hope decreased by T2, yet general anxiety and CGP-specific anxiety also decreased. Receiving actionable results did not impact psychological outcomes at T2. At T2, lower hope, and higher anxiety, depression and CGP-specific anxiety were associated with lower self-efficacy. Psychological and demographic factors (age, socioeconomic status, language, medical occupation, urban living, family history of cancer) independently predicted one or more psychological trajectories. Worse health status and perceived susceptibility to cancer progression predicted hope and anxiety trajectories. Further research on interventions to best support patients undergoing CGP with high anxiety, hopelessness, fear of cancer progression, and poorer health is urgently needed. (PsycInfo Database Record (c) 2022 APA, all rights reserved).